MODEL PENDIDIKAN KARAKTER TERINTEGRASI PEMBELAJARAN SAINS - Sadia, Wayan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2013)
Abstract This research was conducted with the main objective to develop a model of character education integrated with science learning in elementary, junior, and senior high schools. The research was focused on the needs analysis study involving 36 elementary school science teachers, 34 junior high school science teachers and 27 senior high school science teachers to collect information on science learning in relation to character education. Data were collected by questionnaires, observation and interviewing techniques. Data were analyzed by descriptive and qualitative meaning. The results showed that: 1) character education can be developed through selection of science learning model, assessment model, and teaching materials, 2) science learning models that contribute significantly to the development of the character of students are inquiry learning, problem-based learning, cooperative learning , science-technology-society, problem solving, and contextual learning models, 3) science teacher’s responses to the character education are generally very positive and seek to develop good character through a learning process, 4) some (55.3%) science teachers include indicators of character values that to be target of learning in the syllabus and lesson plans, and some (44.7%) do not explicitly specify its, but implicitly implied in the syllabus and lesson plans. Keywords: character education, integrated science learning